Anthropogenic debris in three sympatric seal species of the Western Antarctic Peninsula - Cebuhar, Julieta Denise (2024)
Litter pollution is a growing concern, including for Antarctica and the species that inhabit this ecosystem. In this study, we investigated the microplastic contamination in three seal species that inhabit the Western Antarctic Peninsula: crabeater (Lobodon carcinophaga), leopard (Hydrurga leptonyx) and Weddell (Leptonychotes weddellii) seals. Given the worldwide ubiquity of this type of contaminant, including the Southern Ocean, we hypothesized that the three seal species would present anthropogenic debris in their feces. We examined 29 scat samples of crabeater (n = 5), leopard (n = 13) and Weddell (n = 11) seals. The chemical composition of the items found were identified using micro-Raman and micro-FTIR spectroscopies. All the samples of the three species presented anthropic particles (frequency of occurrence - %FO – 100 %). Fibers were the predominant debris, but fragments and filaments were also present. Particles smaller than 5 mm (micro debris) were predominant in all the samples. Leopard seals ingested significantly larger micro-debris in comparison with the other seal species. The dominant color was black followed by blue and white. Micro-Raman and micro-FTIR Spectroscopies revealed the presenceof different anthropogenic pigments such as reactive blue 238, Indigo 3600 and copper phthalocyanine (blue andgreen). Carbon black was also detected in the samples, as well as plastic polymers such as polystyrene, polyesterand polyethylene terephthalate (PET), polyamide, polypropylene and polyurethane These results confirm thepresence of anthropogenic contamination in Antarctic seals and highlight the need for actions to mitigate theeffects and reduce the contribution of debris in the Antarctic ecosystem.